2018
DOI: 10.1016/j.bpj.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Intranucleus Single-Molecule Imaging in Living Cells

Abstract: Many critical processes occurring in mammalian cells are stochastic and can be directly observed at the single-molecule level within their physiological environment, which would otherwise be obscured in an ensemble measurement. There are various fundamental processes in the nucleus, such as transcription, replication, and DNA repair, the study of which can greatly benefit from intranuclear single-molecule imaging. However, the number of such studies is relatively small mainly because of lack of proper labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Indeed, it is currently the preferred choice for live-cell single molecule imaging. Combined with the development of Cas9-mediated genome-editing (Ran et al, 2013), endogenous Halotagging of proteins has thus become the gold standard (Chong et al, 2018;Hansen et al, 2017;Komatsubara et al, 2019;Rhodes et al, 2017aRhodes et al, , 2017bStevens et al, 2017;Teves et al, 2016aTeves et al, , 2018Youmans et al, 2018), because it avoids the now well-established limitations and potential artifacts associated with protein overexpression (Hansen et al, 2017;Shao et al, 2018;Teves et al, 2016a). Now that we have determined the absolute abundance of CTCF in U2OS cells and cross-validated it using FCS-calibrated confocal imaging ( Figure 1A-D, F),…”
Section: A Simple General Methods For Determining the Abundance Of Halmentioning
confidence: 91%
“…Indeed, it is currently the preferred choice for live-cell single molecule imaging. Combined with the development of Cas9-mediated genome-editing (Ran et al, 2013), endogenous Halotagging of proteins has thus become the gold standard (Chong et al, 2018;Hansen et al, 2017;Komatsubara et al, 2019;Rhodes et al, 2017aRhodes et al, , 2017bStevens et al, 2017;Teves et al, 2016aTeves et al, , 2018Youmans et al, 2018), because it avoids the now well-established limitations and potential artifacts associated with protein overexpression (Hansen et al, 2017;Shao et al, 2018;Teves et al, 2016a). Now that we have determined the absolute abundance of CTCF in U2OS cells and cross-validated it using FCS-calibrated confocal imaging ( Figure 1A-D, F),…”
Section: A Simple General Methods For Determining the Abundance Of Halmentioning
confidence: 91%
“…What is least understood at present is the dynamic nature of nuclear structure and function, which implies a preferred location of chromatin loops and chromatin domains or even entire CTs for the proper execution of functional tasks, including a variable course of channels depending on functional needs. To solve these problems, it will be mandatory to observe movements of DNA sequences and entire CDs between the ANC and INC directly in live cell studies …”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Chromatin dynamics is intimately related to the hierarchical chromatin structure and nuclear functions (Shao et al, 2018). Previous studies have shown that the diffusion dynamics of genomic loci are not mere Brownian motion driven by thermal fluctuation but are often convoluted with active processes such as transcription and DNA repair (Chuang et al, 2006;Dimitrova et al, 2008;Cho et al, 2014;Ochiai et al, 2015;Gu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%